Solitary bone cyst: an analysis of 12 cases - Lilian Cristina Vessoni Iwaki; Liogi Iwaki-Filho; Wilton Mitsunari Takeshita; Mariliani Chicarelli; Luisa de Araújo Moreira Preis; Fernanda Paula Bragatto (Acta Scientiarum. Health Sciences, 2016)
To present further information about SBCs based on a retrospective study of 12 cases, by describing their clinical and radiographic characteristics, and comparing them with recent findings.  The study examined SBCs from the Projeto Lesões Bucais ‘treatment and epidemiology of diseases of the oral cavity’, run at State University of Maringá, Paraná State, Brazil, between 1995 and 2014. Twelve cases were found among the records of 2.424 patients who had been submitted to different types of biopsy. All cases occurred in the mandible, predominantly in patients in the second decade of life, in the region posterior to canines, and among women. All lesions were solitary, 75% of them unilocular. Helicoidal CT showed expansion and rupture of the cortical bone in one case. Differential diagnosis was confirmed by means of histopathological examination. Treatment consisted of surgical exploration in all cases. Most SBCs are usually asymptomatic and diagnosed by chance on routine X-ray examination. However, SBC can cause bone expansion or bone rupture, only visible with more sophisticated imaging systems. This study showed that the diagnosis of SBC benefits with the use of conventional radiography and CT, associated with careful clinical examinations.